Differences Between the Sexes Among Protestant Christian Middle School Students and their Attitudes Toward Science, Technology, Engineering and Math (STEM). Issue 2 (3rd May 2016) - Michael, Kurt Y.; Alsup, Philip R.
ABSTRACT: Research focusing on science, technology, engineering, and math (STEM) education among conservative Protestant Christian school students is scarce. Crenshaw's intersectionality theory is examined as it pertains to religion as a group identifier. The STEM Semantic Survey was completed by 157 middle school students attending six different private Christian schools in Michigan. A MANOVA analysis found a significant difference between male and female students. Post hoc analysis revealed that females had less favorable views of engineering and technology than did their male counterparts. The researchers concluded that attitudes toward STEM among Protestant students are similar to those found in secular schools.